Parents' anxiety and depression symptoms after successful infertility treatment and spontaneous conception: does singleton/twin pregnancy matter?. Issue 10 (17th September 2016) - Tendais, I.; Figueiredo, B.
Abstract : STUDY QUESTION: Does mode of conception [spontaneous/after infertility treatment (IT)], type of pregnancy (singleton/twin) and parent gender have an effect on anxiety and depression levels and trajectories during pregnancy and the post-partum period? SUMMARY ANSWER: Conception after IT was associated with a transitory increase in anxiety during the perinatal period for parents of singletons, while for IT parents of twins higher levels of psychopathological symptoms tended to persist during pregnancy and the post-partum period. WHAT IS KNOWN ALREADY: Most previous studies have shown that successful IT is not associated with poor psychological well-being during pregnancy and the post-partum period, but there is also some evidence for heightened pregnancy-related anxiety, lower self-esteem and lower self-efficacy. Parents of twins experience increased postnatal anxiety and depression. STUDY DESIGN, SIZE, DURATION: This prospective longitudinal study assessed 267 couples ( N  = 534) at each trimester of pregnancy, after childbirth and at 3 months post-partum. PARTICIPANTS/MATERIALS, SETTING, METHOD: The sample comprised 36 couples who had conceived after IT (19 twin pairs and 17 singletons) and 231 couples who had conceived spontaneously (SC; 28 twin pairs and 203 singletons). Couples were recruited at four public hospitals in Portugal, and self-report measures of anxiety and depression symptoms were administered. MAIN RESULTS AND THE ROLE OF CHANCE: IT parents reported higher anxiety after childbirth than parents who SC,  regardless of pregnancy type. IT parents of twins showed higher anxiety at mid-pregnancy, as well as higher anxiety and depression at 3 months post-partum than IT parents of singletons. Among IT mothers, those who had twins exhibited higher depression after childbirth than those who had singletons. Differences according to mode of conception, pregnancy type and parents gender over time were also noted. During pregnancy, IT parents of twins showed no significant change in depression scores, while the other groups depression scores statistically significantly decreased over time. From pregnancy to the post-partum period, (i) IT parents showed an increase in anxiety scores, whereas SC parents exhibited no changes in anxiety scores; (ii) IT women exhibited an increase in depression scores, while SC women depression scores decreased. During the post-partum period, IT and SC parents of twins showed no changes in anxiety scores, while IT and SC parents of singletons anxiety scores declined. LIMITATIONS, REASONS FOR CAUTION: Due to the small number of IT couples, the interpretation and generalization of the results should be done with caution. WIDER IMPLICATIONS OF THE FINDINGS: The adverse impact of IT on psychopathological symptoms depends mostly on time and type of pregnancy, and is greater for twin pregnancies. These findings are important for tailoring interventions that address parents' specific needs at different moments. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by a grant (SFRH/BD/40146/2007) to the first author from the FCT, Foundation for Science and Technology (Portuguese Ministry of Education and Science), by the Operational Program Science and Innovation 2010 (POCI 2010) of the Community Support Board III, by FEDER Funds through the Operational Competitiveness Programme, COMPETE, and through national funding from the FCT under the projects: POCI/SAU-ESP/ 56397/2004 and PTDC/SAU/SAP/116738/2010. The authors have no conflicts of interest.